Estimation of Carbon Stocks in Coffee Plantation in East Java - Aris Wibawa; Fitria Yuliasmara; Rudy Erwiyono (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
Global warming is closely related with the amount of carbon stored in an ecosystem. A research to determine the amount of carbon stock in the coffee farms has been conducted in Sumberbaru and Silo Sub-districts in Jember district, Kaliwining Experimental Station (ES) in Jember district, Sumberasin ES in Malang district and Andungsari ES in Bondowoso district. Carbon stock was measured using the method of Rapid Carbon Stock’s Assessment (RaCSA) developed by ICRAF. Measurements were made on the observation plots of 200 m2, with 3 replications. Results of measurement of carbon stock on coffee plantations showed that the increased carbon stock was proportional with the age of plants. Carbon stock in coffee plantation depends on the shade tree system. In the monoculture coffee leucaena used as shade trees, the carbon stock was lower then in multistrata system (agroforestry) used several kinds of shade trees. Carbon stock on coffee plant in the estate more than smallholder. The average of carbon stock on Robusta coffee at the age of 30 years amounted to 29.38 Mg ha-1, it is greater than the carbon deposit on Arabica coffee that is 22.02 Mg ha-1.Key words: Carbon stock, coffee plantation, Arabica, Robusta, smallholder, agroforestri